Implementing methadone maintenance treatment in prisons in Malaysia. - Wickersham, Jeffrey A; Marcus, Ruthanne; Kamarulzaman, Adeeba; Zahari, Muhammad Muhsin; Altice, Frederick L (Bulletin of the World Health Organization, 2013)
In Malaysia, human immunodeficiency virus (HIV) infection is highly concentrated among people who inject opioids. For this reason, the country undertook a three-phase roll-out of a methadone maintenance treatment (MMT) programme. In Phase 3, described in this paper, MMT was implemented within prisons and retention in care was assessed.
Keywords: Adult; Female; Harm Reduction; Health Plan Implementation; HIV Infections; Humans; Malaysia; Male; Methadone; Opiate Substitution Treatment; Prisons; Substance Abuse, Intravenous